Understanding the property within the eu private law - Slipchenko, A. S.; Сліпченко, А. С.; ORCID: http://orcid.org/0000-0002-2439-4951 (Legal Science and Praxis. - 2021. - № 1. - P. 32-36, 2021)
Досліджено поняття «власність» у розумінні Європейського суду з прав людини. Права та встановлення меж такого розуміння у внутрішніх системах континентального права. Узагальнено теоретичні підходи щодо визначення власності, аналізу та порівняння результатів її тлумачення національними судами та Європейськм судом з прав людини. Наголошено, що поняття власності в межах ст. 1 Протоколу 1 до Конвенції про захист прав людини і основоположних свобод значною мірою збігається із загальним її розумінням у системі правових знань окремих країн романо-германської системи права. Воно охоплює: речі, а також майнові права та обов'язки.

The author of the article studies the concept of “property” in the understanding of the European Court of Human Rights and the establishment of such understanding’s limits in the domestic systems of continental law. Generalization of theoretical approaches in regard to the definition of property, analysis and comparison of the results of its interpretation by national courts and the European Court of Human Rights has made it possible to conclude that the concept of property within the Art. 1 of Protocol 1 to the Convention for the Protection of Human Rights and Fundamental Freedoms largely coincides with its general understanding within the system of legal knowledge of certain countries of the Romano-Germanic law system. It covers: things, as well as property rights and obligations. While defining the application limits of this concept, it has been established that the word “ownership” used in the Art. 1 of Protocol 1 to the Convention to denote economic value as synonymous with the concept of property. Therefore, ownership is any economic benefits (assets), objects of both tangible and intangible world, which are in the state of appropriation by an individual or legal entity. Moreover, the state of appropriation can be consolidated not only by means of property rights, but by other rights (real and obligatory, absolute and relative, etc.).

Исследовано понятие «собственность» в понимании Европейского суда по правам человека. Права и установление границ такого понимания во внутренних системах континентального права. Обобщены теоретические подходы относительно определения собственности, анализа и сравнения результатов ее толкования национальными судами и Европейским судом по правам человека. Отмечено, что понятие собственности в пределах ст. 1 Протокола 1 к Конвенции о защите прав человека и основных свобод в значительной степени совпадает с общим его пониманием в системе правовых знаний отдельных стран романо-германской системы права. Оно включает: вещи, а также имущественные права и обязанности.
Slipchenko, A. S. Understanding the property within the eu private law / Anatoliy Sviatoslavovich Slipchenko // Legal Science and Praxis. - 2021. - № 1. - P. 32-36.
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; власність; ownership; собственность; Міжнародне право .International Law. Международное право; майно; asset; имущество; Європейський суд з прав людини; European Court of Human Rights; Европейский суд по правам человека; об'єкти цивільних прав; objects of civil rights; объекты гражданских прав